Properties and potential use of Irvingia gabonensis and Irvingia wombolu kernel extract as an eco-friendly wood adhesive - Alawode, Abiodun Oluseun (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDFor)--Stellenbosch University, 2019.